Status of BRAC graduates in secondary schools: an exploratory investigation - Khan, Md. Kaisar A (Research and Evaluation Division, Brac, 2019)
This study aimed at examining the status of BRAC graduates in formal secondary schools. Three hundred and twenty BRAC graduates from 20 NFPE schools who were transferred to grade VI in formal schools in 1999 were chosen randomly as programme group. An equal number of non-BRAC students of the same batch from the same secondary schools were chosen randomly as control group. The selected students were interviewed using a structured questionnaire. To assess their level of attainment in secondary schools, marks obtained in the annual examinations in different classes (class VI, VII and VIII) were collected from the concerned schools. Besides, 72 teachers from 8 secondary schools, 6 NFPE teachers, 62 ongoing and 43 dropout students of programme group, 53 ongoing and 21 dropout students of control group were interviewed in-depth. Ninety six guardians of the selected students (55 programme and 41 control groups) and 29 BRAC staff were also interviewed. The study revealed that till June 2002, about 55% ofthe students of the programme group and 73% of the control group were continuing in secondary schools. The rate of continuation for girls of both the groups was higher than boys. Although, the students of the programme group obtained comparatively lower marks than the control group in the school examination, the differences were not statically significant. Both the groups of students felt difficulties mainly in English and Mathematics and the students of programme group felt difficulties with teaching-learning in formal system. The teaching-learning system, economic crisis, involvement in income earning activities and practice of early marriage were the major impediments for continuing study especially for the former BRAC students. It is concluded that unless schools take the leading responsibility in teaching daily lessons in the classrooms, and BRAC's supports are continued at the secondary level, level of retention and attainment of the BRAC graduates in secondary school may not be at an acceptable level.